The diversity of butterflies (Lepidoptera: Rhopalocera) at Tanahbala Island, North Sumatra, Indonesia - Mairawita Mairawita; Study Duha; Henny Herwina (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mairawita, Duha S, Herwina H. 2023. The diversity of butterflies (Lepidoptera: Rhopalocera) at Tanahbala Island, North Sumatra, Indonesia.Biodiversitas 24: 1759-1765. The research was conducted from April to October 2015 to observe the diversity of butterflies (Lepidoptera: Rhopalocera), complete an inventory, and obtain information about biodiversity on Tanahbala Island, South Nias District, North Sumatra Province, Indonesia. Tanahbala Island is a small island in Indonesia with high biodiversity potential. Sampling in the study was carried out in the Fagugu and Tebolo areas with different habitat types, namely forests, forest edges, and residential areas. The tools used to collect samples are cylinder gauze and insect nets. After sampling, 617 butterflies were collected and identified. The identification results showed 52 species of butterflies consisting of 42 genera and nine families. The Nymphalidae family has the most observed species, namely 17, while the Acraeaidae family has only one observed species. The diversity index of all butterflies collected in this study showed a high average value of 3.00. This shows that the biodiversity of butterflies on Tanahbala Island is relatively high. The data obtained from this study will be beneficial to support biodiversity conservation efforts on Tanahbala Island, particularly in managing butterfly habitats. In addition, this data can also be a reference for researchers and conservationists to preserve butterfly biodiversity in Indonesia. This research also shows the importance of inventorying and monitoring biodiversity in Indonesian territory, especially in small islands such as Tanahbala Island, which should be addressed. With better inventory efforts, more complete and accurate data can be produced regarding the biodiversity in Indonesian territory so that more appropriate and effective conservation efforts can be carried out.